A new species of the genus Atopobathynella Schminke, 1973 (Crustacea, Syncarida, Bathynellacea) from the hyporheic zone of the River Godavari, South India - Reddy, Y. Ranga; Drewes, J.; Schminke, H. K. (Zootaxa, 2008)
Atopobathynella Schminke, 1973 is the third genus of Parabathynellidae to be discovered in India. A. operculata sp. n. shows three characters, which are unique within Parabathynellidae: fusion of the inner flagellum of the antennule with the first segment of the outer flagellum, presence of a single seta on the lateral surface of the uropodal sympod, and conspicuous tubes on the labrum. A. operculata sp. n. is also the first species of the genus with an inhomonomous spine row on the uropodal sympod and with an anal operculum almost reaching the end of the furca. Atopobathynella has a Gondwanan distribution, and is being reported for the first time from Asia.